Mobile-Based Graduate Data Information System Design with Framework 7 - Agus Sifaunajah; Moch Khoirul Faizin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Graduates are an inseparable part of an educational institution that can help realize the vision and mission. Besides that, graduates' success in the community can be an indicator of the quality of the education. Therefore, relationships or networks between graduates must be closely intertwined so that later graduates can help each other and share experiences or knowledge with graduates who have just finished their education. Mobile-Based Graduate Data Information System Design with Framework7 is a medium that can facilitate graduates at the Bahrul Ulum Islamic Boarding School Tambakberas Jombang Foundation in recording and collecting graduates spread across various regions. By using the waterfall method as an application design method. This mobile-based application was created to facilitate access to information media according to the current developments. The software used to design this information system is Visual Studio Code, using Mysql as a database and using Framework 7 for mobile application development. With the construction of the Mobile-Based Graduate Data Information System Design, it is hoped that graduates will be able to find out more about graduate data information that is spread out later and can strengthen the synergy between graduates.